Histopathological features and their prognostic impact in nodular lymphocyte‐predominant Hodgkin lymphoma – a matched pair analysis from the German Hodgkin Study Group (GHSG). (26th June 2014) - Hartmann, Sylvia; Eichenauer, Dennis A.; Plütschow, Annette; Mottok, Anja; Bob, Roshanak; Koch, Karoline; Bernd, Heinz‐Wolfram; Cogliatti, Sergio; Hummel, Michael; Feller, Alfred C.; Ott, German; Möller, Peter; et al.
Summary Nodular lymphocyte‐predominant Hodgkin lymphoma (NLPHL) is a rare lymphoma entity. We performed a matched‐pair analysis to evaluate the prognostic impact of several histopathological features in this distinct Hodgkin lymphoma subtype. Lymph node samples of NLPHL patients were tested for CD15, IgD, phosphorylated STAT6, ICOS and Epstein–Barr virus status of the malignant lymphocyte‐predominant cells as well as epithelioid cell clusters and activated T cells in the microenvironment. None of these features was associated with a particular clinical outcome. However, patients presenting with epithelioid cell clusters showed a non‐significant trend towards a lower relapse rate, justifying further evaluation of this marker.